High-gain miniaturized comb-shaped microstrip antenna for 60 GHz band applications: Design and analysis - AbdulGuddoos S.A. Gaid; Mohammed N. Taher; S.N. Abdullah Faisal; Mohammad Ahmed Alomari; Faez M.B. Abdo; Ala’a N.S. Ali; Anas A.G. Mohammed; Ehab F.A. Mahyoub; Eslam T.Y. Mohammed (Results in Optics)
Wireless communication, the backbone of our interconnected world, is playing a crucial role in our daily lives. Antennas, regardless of their design, are essential components of this technology. This research focuses on developing a compact, high-gain antenna optimized for efficient operation in the 60 GHz frequency band. The proposed antenna is constructed using Rogers RT/Duroid 5880 substrate, selected for its low loss (0.0009) and low dielectric constant (2.2). The ground plane and the patch are made of copper with a thickness of 0.035 mm. The antenna is fed via a microstrip line, and to enhance its performance, four slits are incorporated into the radiating element, creating a comb-like structure. Despite its compact dimensions of 3.8 × 5 × 0.118 mm3, the antenna achieves a bandwidth of 2.34 GHz (from 58.81 to 61.15 GHz) and a peak gain of 9.24 dBi. The proposed design demonstrates a radiation efficiency of 89.5 %, a VSWR of 1.005, and an exceptionally low S11 value of −53.014 dB at the resonance frequency. The antenna was designed and optimized using the CST simulator in the time domain, with the results validated in the frequency domain. The close agreement between the simulations confirms the design’s reliability and accuracy. Furthermore, a time-domain study was performed on the proposed antenna with three configurations, i.e., Face to Face, Face to Side, and Side to Side. The analysis evaluated the transmission coefficient magnitude, phase, and group delay. The results showed that the signal distortion and dispersion are minimal. This work significantly contributes to the advancement of high-speed, short-range communication in the 60 GHz band.